A Decision-Making Tool Based Analysis of Onboard Electricity Storage - (:unkn) unknown (ATLANTIS PRESS, 2021)
Energy has been used in maritime transportation, while fossil fuels began to be used more extensively since the industrial revolution to carry more products and obtain higher propulsion power. However; climate change appeared as one of the striking problem areas around the globe, where the scale and speed of rising concerns about climate change are unfortunately increasing. Greenhouse gas emissions are one of the most significant issues about climate change, including the maritime sector and alternative energy resources like renewables and respective hybrid power systems that are considered to be used in maritime transportation. However there is a big challenge about energy storage in terms of the technology penetration and respective costs. In this paper, the current energy storage technologies on a chemical tanker ship have been analyzed in the Reference Energy System perspective and an alternative scenario has been developed. Rectifiers and batteries are the available energy storage systems which are used in case of blackout and emergencies. Low voltage direct current fed systems are GMDSS, emergency lighting, bridge navigational instruments, etc. Batteries are kept charged by rectifiers to be used in case of emergency or need for temporary power. Current energy storage technologies of a chemical tanker ship were fulfilled via Long-Range Energy Alternatives Planning system and the current situation has been specified by the statistical data, to obtain the base scenario. As an alternative scenario, the required secure and cost-effective level of electricity storage in battery groups has been analyzed, according to IMO regulations and respective technology improvements. The results show that, energy storage is a viable solution to back up the vital navigation systems onboard and alternative resources can supply the electricity for storage purposes to encompass a more secure future, in a cleaner atmosphere.
Keywords: Reference energy system; Energy modelling; Ship energy system analysis; Storage; LEAP; ENERGY-CONSUMPTION